PERAN SIKULA GEUTANYOE DALAM MENSOSIALISASIKAN PENCEGAHAN KEKERASAN DAN PELECEHAN SEKSUAL TERHADAP PEREMPUAN DI KABUPATEN NAGAN RAYA - Rahma Dara; Reni Juliani (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2023)
Sikula Geutanyoe is a forum or place for reporting when cases of violence and sexual harassment occur against women in Nagan Raya District. The purpose of this research is to describe the role of Sikula Geutanyoe in socializing the prevention of violence and sexual harassment in Nagan Raya district. The theory used is Radical Feminist theory because it is in accordance with the research objective, namely to fight for women's rights from acts of sexual violence. The type of research used is descriptive qualitative research. Data collection techniques used in- depth interviews with selected research informants, namely members of Sikula Geutanyoe. The focus of the research is the role and inhibiting factors of Sikula Geutanyoe members in promoting the prevention of violence and sexual harassment against women in Nagan Raya Regency. The results of the study show that Sikula Geutanyoe's role in preventing violence and sexual harassment against women can be seen from the socialization provided to the community regarding sex education. If a victim reports a case of sexual violence to Sikula Geutanyoe, Sikula Geutanyoe's role is to protect the victim in handling the case, to help provide a sense of security, to assist the victim in resolving the case legally and to provide psychological assistance. The occurrence of cases of violence and sexual harassment in Nagan Raya Regency is caused by the large number of women who still lack understanding regarding sex education, do not know how to prevent cases of sexual violence and harassment, and lack of public awareness to report cases of violence and sexual harassment against women. in Nagan Raya Regency.Keywords: Role, Socialization, Violence and Sexual Destruction